2008
DOI: 10.1111/j.1467-9450.2008.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal imagery training in active high jumpers

Abstract: The main purpose of this study was to examine whether the use of internal imagery would affect high jumping performance for active high jumping athletes. Over a period of six weeks, a group of active high jumpers were trained with an internal imagery program for a total of 72 minutes. This group was compared to a control group consisting of active high jumpers that only maintained their regular work-outs during the same time period. Four variables were measured; jumping height, number of failed attempts, take-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 38 publications
4
49
0
5
Order By: Relevance
“…For example, an exploratory study has found that a combination of motor imagery and physical practice can improve the learning of tactical strategies in basketball more than either motor imagery or physical practice alone (Guillot et al 2009). Recent studies have also investigated the differences between novice and expert athletes in mental practice ability in basketball players (Cummings et al 2004), volleyball players (Tomasino et al 2012), archers (Chang et al 2011), golfers (Bernier and Fournier 2010), high jumpers (Olsson et al 2008), gymnasts (Mahoney and Avener 1977;Naito 1994), soccer players (O and Munroe-Chandler 2008), ice skaters (Arvinen- Barrow et al 2008), speed skaters (Oishi and Maeshima 2004), martial artists (Babiloni et al 2010;Moreau et al 2010), and horse jockeys (Callow and Waters 2005). While much of this research is exploratory, numerous studies have shown mental practice (specifically motor imagery) to be a promising indicator of an athlete's success.…”
Section: Defining Motor Imagerymentioning
confidence: 98%
“…For example, an exploratory study has found that a combination of motor imagery and physical practice can improve the learning of tactical strategies in basketball more than either motor imagery or physical practice alone (Guillot et al 2009). Recent studies have also investigated the differences between novice and expert athletes in mental practice ability in basketball players (Cummings et al 2004), volleyball players (Tomasino et al 2012), archers (Chang et al 2011), golfers (Bernier and Fournier 2010), high jumpers (Olsson et al 2008), gymnasts (Mahoney and Avener 1977;Naito 1994), soccer players (O and Munroe-Chandler 2008), ice skaters (Arvinen- Barrow et al 2008), speed skaters (Oishi and Maeshima 2004), martial artists (Babiloni et al 2010;Moreau et al 2010), and horse jockeys (Callow and Waters 2005). While much of this research is exploratory, numerous studies have shown mental practice (specifically motor imagery) to be a promising indicator of an athlete's success.…”
Section: Defining Motor Imagerymentioning
confidence: 98%
“…It is commonly agreed that the positive effects of MI and AO on physical task performance are probably explained by activation of overlapping brain areas during motor execution and MI as well as during motor execution and AO (Grezes, Armony, Rowe, & Passingham, 2003;Jeannerod, 1995Jeannerod, , 2001Olsson, Jonsson, & Nyberg, 2008). Jeannerod postulated the well accepted hypothesis that "the motor system is part of a simulation network that is activated under a variety of conditions in relation to action, either self-intended or observed from other individuals" (Jeannerod, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies analyze the outcome from a mathematical perspective with a specific parametric analysis of distances and angles of the movements, e.g. in golf (Smith et al, 2008) and high jump (Olsson et al, 2008). A small number of researches in sport assess the final score of the movement or the number of successful attempts (Peynircioglu et al, 2000;Ploszay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the following, training phase, players in the MI group received a Mp3 file containing audio instructions which were designed to facilitate mental rehearsal of the lay-up shot. As suggested by previous research (Olsson, 2008), participants were instructed to mentally practice three times a week. Each mental practice session consisted of five repetitions and lasted 10 minutes for a total amount of 30 minutes per week.…”
Section: Methodsmentioning
confidence: 99%